Effect of fibers in reinforced concrete deep beams with web opening - Rasheed Abed, Hammood (2020)
Openings in reinforced concrete beams are often needed to provide passage for utility ducts that accommodate essential services such as power supply, water supply, airconditioning and sewerage. The openings have practical necessities but they have negative effects on structure behaviour. The present study aims to investigate the structural performance of fibres and analysis the effect of fibres contented in the reinforced concrete deep beam with web opening. Test variables were different web opening. The openings were one square with size150 mm x150 mm and one rectangular with size 300 mm x150 mm located at either the mid-span or the end span of the deep beam. Two types of fibres considered in this study included steel and hybrid (50% steel-50% kenaf) fibres. Forty-two simply supported deep beam with dimensions of 125 mm x 450 mm x 1200 mm were constructed and tested to failure under four-point loading. One of these deep beams was tested without any web opening and without any addition of fibres to serve as a reference to study the effect of the presence of openings on deep beams with web opening. The fibres were added at the volume fractions of 0%, 1% and 2%. The test results indicated that, the addition of single and hybrid fibres to reinforce concrete deep beams have a significant contribution to improve the structural performance of the fibre reinforced concrete deep beams. The use of fibres leads to much slower growth of the critical diagonal cracks and enhances the load-carrying capacity of the deep beam. In terms of provision of openings in web of reinforced concrete deep beams the results showed that the highest reduce in ultimate load among beams with openings was about 33% and 42% due to the square and rectangular openings at end span, respectively comparison of control deep beam without opening. In terms of single steel fibre the results showed that the significant enhancement of the structural performance of reinforced concrete deep beams with square and rectangular opening at mid and end span was about 111 %, 132%, 46% and 72%, respectively with Vf = 1% of steel fibre, meanwhile with Vf = 2% of steel fibre was showed about 105 %, 124%, 70% and 103%, respectively. In terms of hybrid fibre the results was a significant enhancement of the structural performance of fibre reinforced concrete deep beams with the square and rectangular opening at mid and end span was about 87 %, 61%, 63% and 58% respectively, with Vf = 1% of hybrid fibre. While with Vf = 2% of hybrid fibre the results showed the significant enhancement with the square and rectangular opening at mid and end span was about 38 %, 22%, 38% and 40%, respectively. This investigation demonstrated the ability of reinforced concrete deep beams with web opening using single and hybrid fibres to regain the deep beams capacity, using most economical resources (eco-friendly). Finally, the finding exhibited a significant enhancement of the structural capacity of reinforced concrete deep beams with web opening with Vf = 1% of hybrid fibre.